Method for preparing silane coupling agent Si75 from H2S tail gas absorption liquid

By absorbing the H2S exhaust gas generated in the production process of silane coupling agent Si75 into a sodium hydrosulfide solution and used to prepare Si75, the problems of exhaust gas treatment and resource utilization are solved, and an environmentally friendly and energy-saving production process is achieved.

CN119504831APending Publication Date: 2025-02-25SHANDONG YANGGU HUATAI CHEM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411570315.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

During the production process of the silane coupling agent Si75, the H2S exhaust gas generated poses a threat to workers' health and the environment, and there is a problem of environmental pollution in the exhaust gas treatment.

Method used

By absorbing the H2S tail gas into a sodium hydrosulfide solution and using this solution to prepare the silane coupling agent Si75, the reuse of the tail gas and the recycling of resources are achieved.

Benefits of technology

The synthesis cost of silane coupling agent Si75 is reduced, the problem of exhaust gas treatment is solved, the green and recyclable exhaust gas is realized, and the production process is environmentally friendly and energy-saving.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504831A_ABST
    Figure CN119504831A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a silane coupling agent Si75 from H2S tail gas absorption liquid, which comprises the following steps: mixing a sodium sulfide solution, a buffer solution and NaHS-containing H2S tail gas absorption liquid, then adding elemental sulfur, stirring and reacting to obtain an inorganic phase solution containing polysulfide; the method comprises the following steps: firstly, dropwise adding a phase transfer catalyst solution into an inorganic phase solution containing polysulfide, then dropwise adding gamma-chloropropyltriethoxysilane, and carrying out heat preservation reaction after dropwise adding; and carrying out post-treatment on a mixed product obtained after the reaction to obtain the silane coupling agent Si75. The tail gas absorption liquid is used as the raw material, the raw material is easy to store, low in cost and easy to obtain, the operation process is simple, the process conditions are easy to control, the production period is short, the production cost is low, the yield is high, the average sulfur content of the obtained silane coupling agent Si75 is easy to control, the purity is high, the chromaticity is stable, hydrolysis and sulfur separation are avoided, and the preservation time is long.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a silane coupling agent Si75, in particular to a method for preparing the silane coupling agent Si75 by utilizing tail gas H2S generated in the production process of the silane coupling agent Si75, and belongs to the technical field of organic synthesis. Background Art

[0002] Silane coupling agent is a general term for compounds containing organic functional groups and hydrolyzable silane active groups in the molecule. The purpose of using bifunctional coupling agents is to enhance the compatibility of polar fillers and non-polar rubbers and to improve the interaction between fillers and rubbers. Adding coupling agents to rubber compounds can improve the dispersibility of fillers, and improve the processing properties, physical and mechanical properties, and dynamic properties of the mixed rubber. Materials that utilize these properties include rubber resins, coatings, adhesives, glass, metal surface treatment agents, etc.

[0003] Automobiles are the product of human civilization. While bringing progress to mankind, they also bring many sequelae, among which greenhouse gas emissions are increasingly attracting people's attention. How to reduce energy consumption and reduce exhaust emissions has always been a topic of exploration. Tires, as the driving parts of automobiles, have become a major research direction. Since the tire is in contact with the ground through the tread, studying energy-saving methods from the characteristics of the tread itself has quickly become a hot topic. In 1992, a revolutionary technology appeared in the tire industry: Michelin first introduced the concept of a "green tire", which reduced rolling resistance by 20%, saved 4% of fuel, had a guaranteed mileage of 72,000 kilometers, and had good comprehensive performance. Due to the obvious energy-saving advantages of this tire, it quickly entered the original equipment tire market, mainly the passenger car tire market. So far, almost all major tire companies are competing to adopt this technology, and it is growing at a rate of 20% per year.

[0004] The so-called green tire is a tire reinforced with precipitated silica instead of traditional carbon black. After using this tire, the traction of the car is improved, the operability is improved, and the rolling resistance is reduced (the minimum can be reduced by 50%), thereby reducing fuel consumption (about 5%), improving the grip of the tire in rainy days, and improving ride comfort. Due to the characteristics of silica itself, silane coupling agents must be used in the tire rubber formula to form a strong network between the filler and the rubber. It is well known that sulfur-containing silane coupling agents have always been an indispensable auxiliary agent in the rubber processing process, especially polysulfur silane coupling agents, which are mainly used to improve the dispersibility of inorganic fillers in rubber and improve the bonding between inorganic fillers and rubber, thereby improving the comprehensive performance of rubber. According to the product catalogs, numerous patents and research papers of major silane coupling agent suppliers, the commonly used sulfur-containing silane coupling agents on the market are bis(triethoxysilylpropyl)tetrasulfide (TESPT), bis(triethoxysilylpropyl)disulfide (TESPD), Si-747, NXT, KH580, KH590, VP-Si-363, etc. Among them, polysulfur silane coupling agents are used in the largest amount.

[0005] Silane coupling agent Si75 is widely used as a rubber coupling agent in sulfur-vulcanized or white carbon black-filled rubber compounds. It is suitable for natural rubber, isoprene rubber, styrene-butadiene rubber, butadiene rubber, nitrile rubber, butyl rubber, halogenated butyl rubber, EPDM rubber and rubber compounds of these rubbers. It is used to manufacture tire carcasses, sidewalls, treads, steel wire bonding rubber compounds, transmission outer layer rubber, solid tires, cable insulation and coating materials, rubber rollers and sole materials. After adding silane coupling agent Si75 during the mixing process of rubber, the Mooney viscosity of the rubber compound is significantly reduced and the rheological properties are improved, so it is an ideal processing aid. Silane coupling agent Si75 can significantly improve the physical and processing properties of rubber, improve the dispersibility of fillers in base rubber, reduce the viscosity of the rubber compound, and improve the tear resistance, wear resistance, flex crack resistance and other properties of the vulcanized rubber. In recent years, with the in-depth research on the application performance of silane coupling agent Si75, in addition to the rubber industry, its application areas have expanded to the corrosion resistance research of aluminum alloy surface coatings, electronic and electrical chemicals, special mesoporous materials, special precision casting and other industries.

[0006] In the method of preparing sulfur-containing organic silane using phase transfer catalysis technology, H2S gas is generated during the production process, which is harmful to the health of workers and the environment. The tail gas is absorbed by alkali solution, and the absorbed alkali solution needs to be treated, which causes environmental pollution. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing a silane coupling agent Si75 by using an H2S tail gas absorption liquid. The method absorbs the hydrogen sulfide tail gas generated in the production process of sulfur-containing silane and uses it to prepare the silane coupling agent Si75, thereby reducing costs, realizing resource recycling, solving the problem of tail gas treatment in the production process of sulfur-containing silane, and realizing the green and recyclable use of tail gas.

[0008] The specific technical solutions of the present invention are as follows:

[0009] A method for preparing a silane coupling agent Si75 from a H2S tail gas absorption liquid comprises the following steps:

[0010] (1) mixing a sodium sulfide solution, a buffer solution, and a H2S tail gas absorption liquid containing NaHS, and then adding elemental sulfur, stirring and reacting to obtain an inorganic phase solution containing polysulfide;

[0011] (2) firstly adding a phase transfer catalyst solution to an inorganic phase solution containing polysulfide, and then adding γ-chloropropyltriethoxysilane, and then keeping the temperature for reaction after the addition is complete;

[0012] (3) cooling the mixed product obtained after the reaction in step (2), filtering and separating the liquid to obtain the upper layer, and then cooling and filtering the upper layer, drying by water absorption, adsorbing activated carbon, and filtering to remove the activated carbon to obtain a crude silane coupling agent Si75;

[0013] (4) The crude silane coupling agent Si75 is subjected to reduced pressure distillation to obtain silane coupling agent Si75.

[0014] Furthermore, in step (1), the H2S tail gas absorption liquid containing NaHS can be obtained by passing the H2S tail gas into a sodium hydroxide solution for absorption, and hydrogen sulfide reacts with sodium hydroxide to form sodium hydrosulfide. Wherein, the H2S tail gas can be the tail gas generated in any chemical production process. Preferably, the H2S tail gas is the tail gas generated in the production process of sulfur-containing silanes, such as the tail gas generated in the production process of mercaptopropyltriethoxysilane, and the tail gas generated in the Si75 synthesis production process, and the main component of the tail gas is hydrogen sulfide gas. Wherein, the concentration of the sodium hydroxide solution can be 12 to 35wt%, for example, 12%, 15%, 20%, 25%, 30%, 35%.

[0015] Furthermore, in step (1), the requirements for the H2S tail gas absorption liquid containing NaHS are: NaHS content is 10-32wt%, NaOH content is less than 0.5wt%, and Fe ion content is less than 30ppm. When the sodium hydroxide content in the tail gas absorption liquid is greater than or equal to 0.5wt%, its content can be reduced by continuing to introduce H2S tail gas into the absorption liquid, and when the Fe ion content is greater than or equal to 30ppm, its content can be reduced by controlling the iron ion content of the raw materials and the material of the absorption device, that is, controlling the introduction method of Fe ions.

[0016] Further, in step (1), the buffer is a solution of at least two of sodium phosphate, potassium phosphate, sodium hydrogen phosphate, potassium hydrogen phosphate, sodium dihydrogen phosphate, potassium dihydrogen phosphate, sodium borate, potassium borate, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, and sodium sulfite and water, such as sodium phosphate-sodium borate buffer, sodium phosphate-sodium carbonate buffer, sodium phosphate-sodium hydrogen phosphate buffer, etc. The concentration of the buffer is generally 0.005-0.5 mol / L, such as 0.05 mol / L, 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, 0.35 mol / L, 0.4 mol / L, 0.45 mol / L, 0.5 mol / L.

[0017] Furthermore, in step (1), there is no special requirement for the concentration of the sodium sulfide solution. For the purpose of reducing wastewater discharge, the concentration can be 10 to 45 wt%, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%.

[0018] Furthermore, in step (1), the molar ratio of elemental sulfur: (the total amount of sodium sulfide and sodium hydrosulfide) is 1.1 to 1.4: 1, for example, 1.1: 1, 1.2: 1, 1.3: 1, 1.4: 1. There is no special requirement for the amount relationship between sodium sulfide and sodium hydrosulfide.

[0019] Furthermore, in step (1), the molar ratio of the buffer to the total molar amount of sodium sulfide and sodium hydrosulfide is 0.1 to 0.4:1, for example, 0.1:1, 0.2:1, 0.3:1, 0.4:1.

[0020] Furthermore, in step (1), the reaction temperature is 35 to 95° C., for example, 35° C., 40° C., 45° C., 50° C., 55° C., 60° C., 65° C., 70° C., 75° C., 80° C., 85° C., 90° C., 95° C. The reaction time is generally 5 to 60 min. After the reaction, a reddish brown inorganic phase solution containing polysulfide is obtained.

[0021] Furthermore, in step (1), the reaction is carried out under stirring at a stirring speed of 200 to 800 r / min, for example, 200 r / min, 300 r / min, 400 r / min, 500 r / min, 600 r / min, 700 r / min, 800 r / min.

[0022] Furthermore, in step (2), the phase transfer catalyst is at least one of benzyltriethylammonium chloride, trioctylmethylammonium chloride, triethylhexylammonium bromide, triethyloctylammonium bromide, tetramethylammonium bromide, tetrabutylammonium iodide, tetrabutylammonium chloride, tetrabutylammonium bromide, benzyltriethylammonium chloride, benzyltriethylammonium bromide, dodecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, 18-crown-6, 15-crown-5, polyethylene glycol dialkyl ether, hexabutylguanidine chloride, hexabutylguanidine bromide, hexaethylguanidine bromide, tripiperidylguanidine chloride, and tripiperidylguanidine bromide.

[0023] Furthermore, in step (2), the amount of phase transfer catalyst used is 0.5-10% of the mass of γ-chloropropyltriethoxysilane, for example 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.

[0024] Furthermore, in step (2), the phase transfer catalyst is added dropwise in the form of an aqueous solution. The concentration of the solution has no special requirement and can be 1 to 20 wt%, such as 1%, 5%, 10%, 15%, or 20%.

[0025] Furthermore, in step (2), the molar ratio of γ-chloropropyltriethoxysilane to sodium polysulfide is 1.7 to 2.2:1.

[0026] Further, in step (2), the dropping temperature and the insulation temperature of the phase transfer catalyst solution and γ-chloropropyltriethoxysilane are both 50-95°C, for example, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C. The dropping time of the phase transfer catalyst solution is 1-30min, for example, 1min, 5min, 10min, 15min, 20min, 25min, 30min. The dropping time of γ-chloropropyltriethoxysilane is 0.5-2.5h, for example, 0.5h, 1h, 1.5h, 2h, 2.5h. After the γ-chloropropyltriethoxysilane is dripped, the insulation reaction is continued, samples are taken at regular intervals and analyzed by gas chromatography, and the heating can be stopped when the content of γ-chloropropyltriethoxysilane in the reactant is constant, and the reaction is terminated. The dropping and reflux reactions are carried out under stirring at a speed of 300 to 1200 r / min, for example, 300 r / min, 400 r / min, 500 r / min, 600 r / min, 700 r / min, 800 r / min, 900 r / min, 1000 r / min, 1100 r / min, and 1200 r / min.

[0027] Furthermore, in step (3), the mixed product obtained after the reaction in step (2) is cooled at -10 to 5°C (preferably -10 to 0°C) for 0.5 to 2 hours to promote stratification, and then filtered to remove solid impurities. The combined upper liquid is cooled at -20 to -10°C (preferably -15 to -10°C) for 0.5 to 2 hours, and then filtered to remove salt substances dissolved in the organic phase.

[0028] Furthermore, in step (3), the organic phase is dried using a water-absorbing resin or anhydrous sodium sulfate, and activated carbon is added to the dried organic phase to adsorb tiny impurity particles, the amount of activated carbon used is 0.5-10% of the mass of γ-chloropropyltriethoxysilane, the activated carbon treatment temperature is 25-95°C, the treatment time is 5-120min, and the stirring speed is 200-1000r / min. After the activated carbon treatment is completed, the activated carbon is filtered to remove the activated carbon to obtain a crude silane coupling agent Si75.

[0029] Furthermore, in step (4), during the reduced pressure distillation, the vacuum degree is greater than or equal to -0.09 MPa, for example, -0.09 to -0.1 MPa, and the silane coupling agent Si75 is obtained by distillation at a temperature of 70 to 160°C.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] 1. The entire process of synthesizing the silane coupling agent Si75 of the present invention is carried out in the water phase, which is energy-saving and environmentally friendly.

[0032] 2. The present invention uses sodium hydroxide solution to recover hydrogen sulfide tail gas to obtain sodium hydrosulfide solution, and then uses the solution to prepare Si75, thereby achieving the purpose of recycling the tail gas absorption liquid, solving the tail gas treatment problem, and reducing the synthesis cost of the silane coupling agent Si75.

[0033] 3. The present invention uses a buffer to control the pH value of the solution phase, thereby preventing the hydrolysis and gelation of the raw material γ-chloropropyltriethoxysilane and the generation of by-product hydrogen sulfide.

[0034] 4. The raw materials of the method of the present invention are easy to store, cheap and easy to obtain, the operation process is simple, the process conditions are easy to control, the production cycle is short, the production cost is low, and the yield is high. The average sulfur content of the obtained silane coupling agent Si75 is easy to control, the purity is high, the color is stable, it does not hydrolyze, does not precipitate sulfur, and has a long storage time. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The HPLC chromatogram of the product obtained in Example 1 is shown in FIG.

[0036] Figure 2 The HPLC chromatogram of the product obtained in Example 2 is shown in FIG.

[0037] Figure 3 The high performance liquid chromatogram of the product obtained in Example 3 is shown in FIG.

[0038] Figure 4 The high performance liquid chromatogram of the product obtained in Comparative Example 1 is shown in FIG.

[0039] Figure 5 The high performance liquid chromatogram of the product obtained in Comparative Example 2 is shown in FIG.

[0040] Figure 6 The high performance liquid chromatogram of the product obtained in Comparative Example 3 is shown in FIG. DETAILED DESCRIPTION

[0041] The technical solution of the present invention is further described below in conjunction with specific embodiments, but these embodiments should not be construed as limiting the technical solution.

[0042] Unless otherwise specified, the following concentrations are all mass percentages.

[0043] Preparation of NaHS tail gas absorption liquid

[0044] Take three conical flasks, respectively fill them with a sodium hydroxide solution with a concentration of 16wt%, and install a thermometer in the range of 100℃ to monitor the temperature change, and assemble into a three-stage tail gas absorption device; slowly pass the H2S tail gas generated in the Si75 synthesis production process from the bottom into the first-stage tail gas absorption bottle, observe the temperature change in the first-stage tail gas absorption conical flask, and stop passing the tail gas when the temperature does not rise and remains unchanged. The sodium hydrosulfide, sodium hydroxide and iron ion contents of the tail gas absorption liquid obtained in the first conical flask were detected by the GB / T23937-2020 method, which were 15.0% NaHS, 0.1% NaOH, and 10ppm Fe ions, respectively.

[0045] Take 6 beakers, numbered ① to ⑥, the tail gas absorption liquid in beaker ① is the absorption liquid obtained above, and the component content is: 15.0% NaHS, 0.1% NaOH, 10ppmFe ion, and the absorption liquid is used in Example 1; the tail gas absorption liquid in beaker ② is added with an appropriate amount of sodium hydroxide on the basis of the absorption liquid in beaker ①, so that the content of each component is: 15.0% NaHS, 0.2% NaOH, 10ppmFe ion, and the absorption liquid is used in Example 2; the tail gas absorption liquid in beaker ③ is added with an appropriate amount of ferric chloride on the basis of the absorption liquid in beaker ①, so that the content of each component is: 15.0% NaHS, 0.1% NaOH, 15ppmFe ion, and the absorption liquid is used in Example 3; ④ The tail gas absorption liquid in beaker No. 1 was added with an appropriate amount of sodium hydroxide on the basis of the absorption liquid in beaker No. 1, so that the contents of each component were: 15.0% NaHS, 0.6% NaOH, 10ppmFe ions, and the absorption liquid was used for Comparative Example 1; the tail gas absorption liquid in beaker No. 5 was added with an appropriate amount of ferric chloride on the basis of the absorption liquid in beaker No. 1, so that the contents of each component were: 15.0% NaHS, 0.1% NaOH, 50ppmFe ions, and the absorption liquid was used for Comparative Example 2; the tail gas absorption liquid in beaker No. 6 was added with an appropriate amount of sodium hydroxide and ferric chloride on the basis of the absorption liquid in beaker No. 1, so that the contents of each component were: 15.0% NaHS, 0.6% NaOH, 50ppmFe ions, and the absorption liquid was used for Comparative Example 3.

[0046] Preparation of silane coupling agent Si75

[0047] Example 1

[0048] A method for preparing a silane coupling agent Si75 in an aqueous phase comprises the following steps:

[0049] 1. Dissolve sodium phosphate and sodium borate in water to prepare a buffer solution with a sodium phosphate concentration of 0.05 mol / L and a sodium borate concentration of 0.05 mol / L; dissolve sodium sulfide pentahydrate in water to prepare a sodium sulfide solution with a mass fraction of 12%.

[0050] 2. Mix 95g of 12% sodium sulfide solution, 150g of 15% NaHS tail gas absorption liquid (NaOH content 0.1%, Fe ion content 10ppm) and 230g of buffer solution, and add elemental sulfur thereto, the molar ratio of elemental sulfur to the sum of sodium sulfide and NaHS is 1.15:1, stir at 70°C at a speed of 280r / min until dissolved, and keep warm for 45min to obtain 490g of a reddish brown inorganic phase solution containing polysulfide, and the polysulfide content is 12% as detected by gas chromatography-mass spectrometry;

[0051] 3. Dissolve dodecyltrimethylammonium bromide in water to prepare a catalyst solution with a mass fraction of 1%. Add the catalyst solution dropwise to the inorganic phase solution containing polysulfide at 75°C and a stirring speed of 380r / min for 10 minutes. Then, add γ-chloropropyltriethoxysilane with a purity of more than 98% dropwise for 1 hour. The molar ratio of γ-chloropropyltriethoxysilane to sodium polysulfide is 2:1. The amount of dodecyltrimethylammonium bromide added is 1% of the mass of γ-chloropropyltriethoxysilane. After the addition is completed, continue to keep the reaction warm, take samples at regular intervals and analyze the samples by gas chromatography. Stop heating when the content of γ-chloropropyltriethoxysilane is constant in the reactants.

[0052] 4. Cool the mixed product obtained in step 3 in an environment of 0°C for 0.5h, filter to remove solid impurities, and then separate the liquids to take the upper liquid for use; add an appropriate amount of sodium chloride to the lower liquid and let it stand for stratification, take the upper liquid, combine the upper liquids recovered twice and then cool to -10°C, cool for 0.5h, filter to remove the salt substances dissolved in the organic phase, and then dry with a water-absorbing resin or anhydrous sodium sulfate, add activated carbon to the dried organic phase to adsorb tiny impurity particles, the amount of activated carbon is 1% of the mass of γ-chloropropyltriethoxysilane, the treatment temperature is 25°C, the treatment time is 10min, the stirring speed is 300r / min, and after treatment, filter to obtain crude silane coupling agent Si75.

[0053] 6. The crude silane coupling agent Si75 was subjected to reduced pressure distillation operation with a vacuum degree of 0.1 MPa and a temperature of 75°C to obtain the silane coupling agent Si75.

[0054] The reaction time of the whole process of this embodiment is about 3 hours. After calculation, the product yield is 97%, and the product yield = the mass of the product obtained by vacuum distillation / the mass of the silane coupling agent theoretically obtained based on the amount of γ-chloropropyltriethoxysilane input. After detection by gas analyzer, the purity of the silane coupling agent Si75 product finally obtained by vacuum distillation is above 99%.

[0055] Example 2

[0056] The silane coupling agent Si75 was prepared according to the method of Example 1, except that the NaHS tail gas absorption liquid used had a NaHS content of 15wt%, a NaOH content of 0.2%, and a Fe ion content of 10ppm. The product yield was calculated to be 96%, the purity of the product was more than 99%, and the product was light yellow in color.

[0057] Example 3

[0058] Silane coupling agent Si75 was prepared according to the method of Example 1, except that the NaHS tail gas absorption liquid used had a NaHS content of 15wt%, a NaOH content of 0.1%, and a Fe ion content of 15ppm. The product yield was calculated to be 96.5%, the purity of the product was above 99%, and the product was light yellow in color.

[0059] Comparative Example 1

[0060] Silane coupling agent Si75 was prepared according to the method of Example 1, except that the NaHS tail gas absorption liquid used had a NaHS content of 15wt%, a NaOH content of 0.6%, and a Fe ion content of 10ppm. According to calculation, the product yield was 94%, the purity of the product was more than 99%, and a small amount of hydrolyzed floccules appeared in the product and the chromaticity was heavy.

[0061] Comparative Example 2

[0062] The silane coupling agent Si75 was prepared according to the method of Example 1, except that the NaHS tail gas absorption liquid used had a NaHS content of 15wt%, a NaOH content of 0.1%, and a Fe ion content of 50ppm. The product yield was calculated to be 94.5%, and the purity of the product was above 99%, but the chromaticity was heavy.

[0063] Comparative Example 3

[0064] Silane coupling agent Si75 was prepared according to the method of Example 1, except that the NaHS tail gas absorption liquid used had a NaHS content of 15wt%, a NaOH content of 0.6%, and a Fe ion content of 50ppm. The product yield was calculated to be 93.7%, the purity of the product was above 99%, a small amount of sulfur appeared in the product, and the color was heavy.

[0065] The silane coupling agent Si75 products obtained in the above examples and comparative examples were analyzed, and the results are shown in Table 1. The sulfur chain length, sulfide content, and total sulfur content were detected by high performance liquid chromatography, the ethanol and impurity (impurities other than ethanol) contents were detected by gas chromatography-mass spectrometry, and the chromaticity was detected by an iron-cobalt colorimeter.

[0066] Table 1

[0067]

[0068] It can be seen from the above experimental data that the method of the present invention has short reaction time, high Si75 purity, high yield, stable chromaticity, low raw material residue, and an average sulfur content controlled at 2.05-2.35. The obtained product does not hydrolyze, does not precipitate sulfur, and has a long shelf life.

[0069] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing silane coupling agent Si75 from H2S tail gas absorption liquid, characterized in that The following steps are involved: (1) mixing a sodium sulfide solution, a buffer solution, and a H2S tail gas absorption liquid containing NaHS, and then adding elemental sulfur, stirring and reacting to obtain an inorganic phase solution containing polysulfide; (2) firstly adding a phase transfer catalyst solution to an inorganic phase solution containing polysulfide, and then adding γ-chloropropyltriethoxysilane, and then carrying out a heat-insulating reaction after the addition is complete; (3) cooling the mixed product obtained after the reaction in step (2), filtering and separating the liquid to obtain the upper layer, and then cooling and filtering the upper layer, drying by water absorption, adsorbing activated carbon, and filtering to remove the activated carbon to obtain a crude silane coupling agent Si75; (4) The crude silane coupling agent Si75 is subjected to reduced pressure distillation to obtain silane coupling agent Si75.

2. The method according to claim 1, characterized in that: In step (1), at least one of the following conditions is included: Condition 1: In the H2S tail gas absorption liquid containing NaHS, the NaHS content is 10-32wt%, the NaOH content is less than 0.5wt%, and the Fe ion content is less than 30ppm; Condition 2: The concentration of the sodium sulfide solution is 10-45 wt%; Condition 3: The buffer solution is a solution of at least two of sodium phosphate, potassium phosphate, sodium hydrogen phosphate, potassium hydrogen phosphate, sodium dihydrogen phosphate, potassium dihydrogen phosphate, sodium borate, potassium borate, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, and sodium sulfite in water; Condition 4: The concentration of the buffer solution is 0.005-0.5 mol / L; Condition 5: the molar ratio of elemental sulfur: sodium sulfide and sodium hydrosulfide is 1.1-1.4:1; Condition 6: The total molar ratio of the buffer to sodium sulfide and sodium hydrosulfide is 0.1-0.4:

1.

3. The method according to claim 1 or 2, characterized in that: In step (1), the H2S tail gas absorption liquid containing NaHS is obtained by passing the H2S tail gas into a sodium hydroxide solution for absorption; preferably, the concentration of the sodium hydroxide solution is 12 to 35 wt %; preferably, the H2S tail gas is the tail gas generated in the production process of sulfur-containing silane.

4. The method according to claim 1 or 2, characterized in that: In step (1), the reaction temperature is 35-95° C., the reaction time is 5-60 min, and the stirring speed is 200-800 r / min.

5. The method according to claim 1, characterized in that: In step (2), the phase transfer catalyst is at least one of benzyltriethylammonium chloride, trioctylmethylammonium chloride, triethylhexylammonium bromide, triethyloctylammonium bromide, tetramethylammonium bromide, tetrabutylammonium iodide, tetrabutylammonium chloride, tetrabutylammonium bromide, benzyltriethylammonium chloride, benzyltriethylammonium bromide, dodecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, 18-crown-6, 15-crown-5, polyethylene glycol dialkyl ether, hexabutylguanidine chloride, hexabutylguanidine bromide, hexaethylguanidine bromide, tripiperidylguanidine chloride, and tripiperidylguanidine bromide.

6. The method according to claim 1 or 5, characterized in that: In step (2), the amount of phase transfer catalyst used is 0.5-10% of the mass of γ-chloropropyltriethoxysilane; preferably, the concentration of the phase transfer catalyst solution is 1-20wt%.

7. The method according to claim 1 or 5, characterized in that: In step (2), the molar ratio of γ-chloropropyltriethoxysilane to sodium polysulfide is 1.7 to 2.2:

1.

8. The method according to claim 1 or 5, characterized in that: In step (2), the dropping temperature and insulation temperature of the phase transfer catalyst solution and γ-chloropropyltriethoxysilane are both 50-95° C., the dropping time of the phase transfer catalyst solution is 1-30 min, and the dropping time of γ-chloropropyltriethoxysilane is 0.5-2.5 h; preferably, the dropping and insulation reactions are carried out under stirring at a stirring speed of 300-1200 r / min.

9. The method according to claim 1, characterized in that: In step (3), the mixed product obtained after the reaction in step (2) is cooled at -10 to 5°C for 0.5 to 2h and then filtered; the combined upper layer liquid is cooled at -20 to -10°C for 0.5 to 2h.

10. The method according to claim 1 or 9, characterized in that: In step (3), drying is performed using a water-absorbing resin or anhydrous sodium sulfate; during activated carbon adsorption, the amount of activated carbon used is 0.5 to 10% of the mass of γ-chloropropyltriethoxysilane, the treatment temperature is 25 to 95° C., the treatment time is 5 to 120 min, and the stirring speed is 200 to 1000 r / min.